Proposal for hybrid passive cooling system of batteries In the electric car - tamaldin, noreffendy; Abdollah, Mohd Fadzli bin (2012)
This paper addresses the challenges faced by Electric Vehicle (EV) thermal management system and proposed a method to overcome them. Due to the non existence of internal combustion engine (ICE) in EV, the driving mechanisms of conventional cooling system need to be revamped. Therefore, in this paper a combination of liquid cooled, air cooled and phase change material (PCM) cooling system was introduced. The main heat dissipation from EV was identified coming from electric motor, battery module and the electronics controller and components. As this is a preliminary study, the reliability and sustainability of the system need to be further investigated. The investigation would include the, simulation and modeling of heat dissipated from the EV and also the cooling capacity of the proposed cooling system.